Pengaruh Good Corporate Governance dan Corporate Social Responsibility Terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Intervening(Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Periode 2021-2023) - Nandita Septiana; Rina Susanti (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study focuses on analysing the significance of the influence of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on company value, using financial performance as a mediating variable. This quantitative study uses secondary data from 63 mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023, selected through purposive sampling. The data collected through literature studies and documentation were then analysed using a series of statistical tests, including classical assumption tests, path analysis, t-tests, F-tests, R² tests, and Sobel tests. The results showed that all variables passed the classical assumption test, meaning that the regression model was valid. Furthermore, path analysis revealed that GCG had a significant effect on financial performance but no significant effect on company value. Conversely, CSR had no significant effect on financial performance but a significant effect on company value, with financial performance also having a significant effect on company value. However, the Sobel test confirmed that financial performance did not successfully mediate the effect of GCG and CSR on company value. On the other hand, the F test confirms that the regression model used is appropriate, although the R² test shows that the independent variables can only explain 10.8% and 23.1% of the variation in company value, while the rest is influenced by factors outside the model.